REFECTO: GeoGebra-based Interactive Media for Light Waves Topic - Aprilia, Nabila; Romadhon, Dzikri Rahmat (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
REFECTO (Recognizing Fundamental Concepts Through Optics) is a GeoGebra-based instructional simulation developed to help students visually understand wave optics concepts, overcoming laboratory limitations while enhancing conceptual mastery and learning outcomes. An R&D framework, employing the 4D model (Define, Design, Develop) across three iterative phases. The Define phase identified pedagogical gaps through literature synthesis and stakeholder interviews. The Design phase integrated multimodal components aligned with learning needs. The Develop phase involved formative validation by five interdisciplinary experts, followed by phased trials with 31 Grade XI students and three physics teachers at SMA FI Jakarta. Data collection combined expert validation metrics and summative assessments. Rigorous analysis included Aiken’s validity index, Cronbach’s alpha reliability using a Likert scale response to measure feasibility and practicality, effectiveness was evaluated using a one-group pretest-posttest design, with data analyzed using n-Gain and Cohen’s d statistics via SPSS. REFECTO demonstrated robust (validity = 0.92; reliability = 0.76). Field testing showed high practicality based on student responses (validity = 0.90; reliability = 0.65) and teacher responses (validity = 0.85; reliability = 0.60), and statistically significant learning gains, with an N-Gain score of 84% (g = 0.84) and large effect size (d = 4.32). This study successfully operationalizes GeoGebra as a transformative tool for physics education, producing REFECTO a validated, scalable resource addressing critical infrastructure limitations in optics instruction. These findings underscore the potential of open-source platforms to bridge pedagogical divides, while supporting active learning as a strategy to improve student learning outcomes.